Influenza epidemiology and influenza vaccine effectiveness during the 2014-2015 season: annual report from the Global Influenza Hospital Surveillance Network - Puig-Barberà, Joan; Burtseva, Elena; Yu, Hongjie; Cowling, Benjamin J; Badur, Selim; Kyncl, Jan; Sominina, Anna; GIHSN (BMC public health, 2016)
The Global Influenza Hospital Surveillance Network (GIHSN) has established a prospective, active surveillance, hospital-based epidemiological study to collect epidemiological and virological data for the Northern and Southern Hemispheres over several consecutive seasons. It focuses exclusively on severe cases of influenza requiring hospitalization. A standard protocol is shared between sites allowing comparison and pooling of results. During the 2014-2015 influenza season, the GIHSN included seven coordinating sites from six countries (St. Petersburg and Moscow, Russian Federation; Prague, Czech Republic; Istanbul, Turkey; Beijing, China; Valencia, Spain; and Rio de Janeiro, Brazil). Here, we present the detailed epidemiological and influenza vaccine effectiveness findings for the Northern Hemisphere 2014-2015 influenza season.
Keywords: Čína; senioři; Seasons; Turecko; Russia; senioři nad 80 let; Population Surveillance; kojenec; Influenza; mladiství; Česká republika; vakcíny proti chřipce; Influenza, Human; Rusko; Middle Aged; mužské pohlaví; Brazil; Turkey; Infant; China; Epidemiological study; Prospective Studies; Adult; Influenza Vaccines; Czech Republic; Adolescent; surveillance populace; Španělsko; dítě; Child; Aged, 80 and over; Child, Preschool; Infant, Newborn; ženské pohlaví; novorozenec; Humans; předškolní dítě; prospektivní studie; Spain; Vaccine; Brazílie; Virus; lidé středního věku; Surveillance; Hospitalization; hospitalizace; dospělí; Female; Aged; roční období; chřipka lidská; lidé; Male